The Analysis of EFL Teachers’ Perception of Differentiated Instruction - Sentia, Sela; Febriani, Hanura (Yayasan Sembilan Pemuda Indonesia, 2025)
This study analyzes English as a Foreign Language (EFL) teachers' perceptions of differentiated instruction and how they implement it in vocational high school classrooms. This research employed a mixed-method approach, combining quantitative data from questionnaires and qualitative insights from interviews and classroom observations involving two EFL teachers at SMKN 4 Kepahiang, Indonesia. The finding reveals that both teachers have positive perceptions of differentiated instruction and actively implement its core components content, process, and product differentiated despite facing practical challenges such as limited facilities and difficulties in student grouping. The results emphasize that teacher commitment and adaptability play crucial roles in overcoming these obstacles. One teacher relied on structured planning, while the other adapted spontaneously based on the student’s responses. This study provides new insight into the practical implementation of differentiated instruction in the Indonesian EFL context, particularly within the framework of the Merdeka Curriculum. Unlike previous studies, which often focused on theoretical frameworks or small-scale applications of differentiated instruction in conventional curricula, this research emphasizes its application in the context of a nationally mandated, student-centered curriculum reform. Its main contribution lies in highlighting the importance of teacher perception, readiness, and contextual flexibility, while recommending institutional support and continuous professional development to enhance inclusive teaching practices.